Synthesis and characterization of geminis and implications of their micellar solution on ninhydrin and metal amino acid complex - Dileep Kumar; Malik Abdul Rub; Abdullah M. Asiri (Royal Society Open Science, 2020)
In our study, three gemini dicationic surfactants with different methylene group spacer (16-6-16, 16-5-16 and 16-4-16) have been synthesized and characterized in solution by 1H NMR spectroscopic technique. The implications of gemini micellar solution on ninhydrin and metal amino acid complex ([Cu(II)-Trp]+) were performed by the means of single-beam UV–visible spectroscopy. The absorbance was noted at regular time intervals and values of rate constant (kψ) were determined by using a computer-based program. Synthesized surfactants proved as an efficient catalyst on the interaction of ninhydrin with metal amino acid complex as compared with conventional surfactant and aqueous systems. The required description regarding the implications of gemini dicationic surfactants are provided in the text in detail. The conductivity technique was applied in order to get critical micelle concentration (cmc) of geminis in the presence and absence of reactants. Catalytic results developed in gemini dicationic surfactant system were explained effectively by pseudo-phase model. Various thermodynamic quantities, viz., activation energy, Ea, activation enthalpy, ΔH#, and activation entropy, ΔS#, were obtained on interaction of ninhydrin with [Cu(II)-Trp]+ in gemini systems by applying Eyring equation. A detailed explanation about these evaluated parameters was also made.